2014
DOI: 10.1186/1472-6831-14-17
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to adopting and implementing an oral health programme for managing early childhood caries through primary health care providers in Lima, Peru

Abstract: BackgroundTo identify barriers to participation in a primary oral health care programme aimed at preventing early childhood caries, as perceived by nurses.MethodsOf a total of 140 randomly selected nurses employed in 40 government health centres in Lima, 123 completed a pre-tested questionnaire. Background variables were districts’ ‘socio-economic status’ (SES) and ‘years of experience’. Factor analysis was performed. ANOVA was applied for testing the influence of the background variables on the barrier factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[19] In the literature, contradictory results have been obtained from some studies in which education degree is found a significantly effective factor whereas years of professional experience did not significantly influence knowledge. [11] Perassi et al [16] also indicated no significant associations between knowledge vs. socio-economic status and years of professional experience in their study. When considering sociodemographic factors, we did not obtain any significant relations between age, marital status, parental status, type of high school, type of pediatric clinic in which the nurses work, the duration of working life in the same clinic and total mean correct scores.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…[19] In the literature, contradictory results have been obtained from some studies in which education degree is found a significantly effective factor whereas years of professional experience did not significantly influence knowledge. [11] Perassi et al [16] also indicated no significant associations between knowledge vs. socio-economic status and years of professional experience in their study. When considering sociodemographic factors, we did not obtain any significant relations between age, marital status, parental status, type of high school, type of pediatric clinic in which the nurses work, the duration of working life in the same clinic and total mean correct scores.…”
Section: Discussionmentioning
confidence: 64%
“…Pesaressi et al [16] reported similar results including the poorer knowledge status, particularly in the knowledge of "experience in seeing carious lesions" and "the knowledge on caries prevention". In the literature, it has also been reported that the rudimentary knowledge level of nurses regarding children's oral health care is inevitable due to the fact that education on specific oral health issues has not been implemented in their continuous education period.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations